2020
DOI: 10.3390/jcm9051331
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Circulating CD4+ T Cell Subsets in Patients with Mycobacterium avium Complex Pulmonary Disease

Abstract: Although prevalence of Mycobacterium avium complex pulmonary disease (MAC-PD) is increasing, limited data are available regarding vulnerability to Mycobacterium avium complex (MAC) infections. To understand the pathobiology of interaction between MAC and host-immunity, it is important to understand the characteristics for circulating T cells in terms of the immunological phenotype and functional correlates in MAC-PD. We aimed to characterize immunophenotype, cytokine profile, and immune inhibitory receptors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…The above-mentioned results were corroborated by findings recently provided by Han et al [42], who investigated the characteristics of circulating CD4 + T-cell subsets in a subject affected by MAC pulmonary disease, performing a prospective case-control study on 71 NTM-LD individuals and 20 HDs. The authors stimulated PBMCs with heat-killed M. avium and M. intracellulare bacilli and evaluated CD4 + T-cell populations.…”
Section: Immune Exhaustion In Ntm Infectionsupporting
confidence: 82%
See 1 more Smart Citation
“…The above-mentioned results were corroborated by findings recently provided by Han et al [42], who investigated the characteristics of circulating CD4 + T-cell subsets in a subject affected by MAC pulmonary disease, performing a prospective case-control study on 71 NTM-LD individuals and 20 HDs. The authors stimulated PBMCs with heat-killed M. avium and M. intracellulare bacilli and evaluated CD4 + T-cell populations.…”
Section: Immune Exhaustion In Ntm Infectionsupporting
confidence: 82%
“…It should be underlined how only a minority (2/30, 6.6%) of subjects were treatment naïve, with 19/30 (63.3%) under therapy at the time of sampling, an important confounding factor that does not allow drawing solid conclusions about IE in this cohort. Nonetheless, the attenuated IL-17 response might contribute to host vulnerability or pathogen evasion via impairment of neutrophil recruitment and granulopoiesis [42]. Figure 1 provides a general overview of the IE process among patients with NTM-LD.…”
Section: Immune Exhaustion In Ntm Infectionmentioning
confidence: 99%
“…Moreover, the partial block of PD-1 and the PD ligand with antagonizing antibodies significantly increased the cytokine production of IFN-γ and decreased the expression of apoptosis markers on T lymphocytes, highlighting how immune checkpoint pathways modulate T cell responses during MAC-LD ( 74 ). These results have been corroborated by Han et al., who highlighted an increase in PD-1, CTLA-4, and TIM-3 expression on CD4+ T cells in MAC-LD individuals after NTM-antigens stimulation ( 75 ) and Wang et al., who showed that in patients with NTM-LD, TIM-3 expression increased over CD4+ and CD8+ T cells and correlated with cell apoptosis and a reduction in specific cytokine production (IL-2, INF-γ, TNF-α) ( 76 ). In addition, Shu et al.…”
Section: Conventional T Cells and Immune Exhaustionsupporting
confidence: 67%
“…Han et al ( 14 ) determined the phenotype of blood CD4 + T cells in 71 patients with NTM-LD due to MAC and 20 healthy controls following stimulation of their PBMC with heat-killed MAC. Compared to cells from control subjects, the stimulated PBMC of patients with MAC lung disease had decreased total CD4 + T cells and decreased T H 17 cells but there were increased number of T H 2 cells (CD4 + IL-4 + ), Tregs, and CD4 + T cells that expressed deactivation or exhaustion markers PD-1, CTLA-4, and TIM-3.…”
Section: Resultsmentioning
confidence: 99%